Preliminary observations regarding the expectations, acceptability and satisfaction of whole-body MRI in self-referring asymptomatic subjects - Busacchio, Derna; Mazzocco, Ketti; Gandini, Sara; Pricolo, Paola; Masiero, Marianna; Summers, Paul Eugene; Pravettoni, Grabriella; Petralia, Giuseppe (British journal of radiology, 2021)
To evaluate the satisfaction of asymptomatic subjects who self-referring Whole-Body Magnetic Resonance Imaging (WB-MRI) for early cancer diagnosis. Subjects completed a pre-examination questionnaire, while waiting for their WB-MRI examination, recording demographics, expected discomfort, perceived knowledge and usefulness of the procedure and health risk perceptions, as well as a post-examination questionnaire, measuring discomfort experienced, acceptability and satisfaction with WB-MRI. We examined which factors influenced discomfort and satisfaction associated with WB-MRI. 65 asymptomatic subjects (median age 51; 29 females) completed the questionnaire. Before WB-MRI, 29% of subjects expected discomfort of some form with claustrophobia (27.7%) and exam duration (24.6%) being the most common concerns. Experienced discomfort due to shortness of breath was significantly lower than expected. This difference was significantly associated with the personal risk perception to get a disease ( = 0.01) and educational level ( = 0.002). More specifically, higher level of perceived personal risk of getting a disease and lower level of education were associated with higher expected than experienced discomfort. Similarly, experiencing less claustrophobia than expected was significantly associated with gender ( = 0.005) and more pronounced among females. A majority (83%) of subjects expressed high levels of satisfaction with WB-MRI for early cancer diagnosis and judged it more acceptable than other diagnostic exams. Asymptomatic subjects self-referring to WB-MRI for early cancer diagnosis showed high levels of satisfaction and acceptability with the examination. Nevertheless, a relevant proportion of participants reported some form of discomfort. Interestingly, participants with higher perceived personal risk to get a disease, lower education and females showed to expect higher discomfort than experienced. Scope exists for measures to assess expected feelings and develop personalized interventions to reduce the stress anticipated by individuals deciding to undergo WB-MRI for early cancer diagnosis.